Dual actions of the antioxidant chlorophyllin, a glutathione transferase P1‐1 inhibitor, in tumorigenesis and tumor progression. Issue 5 (28th November 2018) - Ozcan, Mehmet; Esendagli, Gunes; Musdal, Yaman; Canpinar, Hande; Bacanlı, Merve; Anlar, Hatice Gul; Esendağlı‐Yılmaz, Güldal; Beyramzadeh, Mojtaba; Aksoy, Yasemin
Abstract: Glutathione (GSH) and enzymes related to this antioxidant molecule are often overexpressed in tumor cells and may contribute to drug resistance. Blockade of glutathione transferases (GSTs) has been proposed to potentiate the efficacy of chemotherapeutic drugs in cancer. The aim of this study was to evaluate the effect of chlorophyllin that has antioxidant properties, and also interferes with the activity of GST P1‐1, on breast cancers in vitro and in vivo. The in vivo studies were conducted using an N ‐methyl‐ N ‐nitrosourea (MNU)‐induced chemical carcinogenesis model in laboratory rats. DNA damage, GST activity, and GSH levels were determined in liver and tumor tissues. Treatment with chlorophyllin increased the GSH levels in the liver and significantly decreased DNA damage in the blood, liver, and tumor tissues. Even though tumorigenesis was delayed in rats receiving chlorophyllin before MNU injections, once the tumors emerged, the progression of tumor appeared to be faster than in the animals that received the carcinogen only. Out of nine breast cell lines, GST P1‐1 expression was detected in MCF‐12A, MDA‐MB‐231, and HCC38. Concomitant incubation with chlorophyllin and docetaxel did not significantly affect cell proliferation and viability. Chlorophyllin displayed genoprotective effects that initially delayed tumorigenesis. However, once the tumors were established, it may act as a promoter that facilitates tumor growth, potentially by a mechanism independent of cell proliferation and viability. Our results underline the pros and cons of antioxidant treatment in cancer, even if it has a capacity to inhibit GST P1‐1. Abstract : Chlorophyllin displayed genoprotective effects that can initially delay tumorigenesis; however, once the tumors are established, it may act as a promoter that facilitates tumor growth, potentially by a mechanism independent of cell proliferation and viability. Our results underline the pros and cons of antioxidant treatment in cancer, even if it has a capacity to inhibit GST enzyme.